2020
DOI: 10.1108/f-09-2019-0104
|View full text |Cite
|
Sign up to set email alerts
|

Data center maintenance: applications and future research directions

Abstract: Purpose One of the most critical infrastructures is a data center (DC) because of it having many servers, computers and other equipment. DCs provide online services for various companies in the information technology (IT) industry. DC facilities should provide reliable online services while addressing the required quality and performance level considering maximum reliability and availability. The purpose of this study is to represent and classify the main findings in this area and to identify the main research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…In the field of Generation Planning, a gradual transition from the 'Bottom Up' strategy (based on what is easily feasible) to the 'Top Down' approach is required (based on the desired level of performance) (The World Bank, 2009). Abadi et al (2020) have classified the main studies in O&M management and used surveys to describe their findings and to represent future research opportunities in this field. Their study revealed the most frequently used terms in articles on O&M management in the Engineering Village -Elsevier database.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the field of Generation Planning, a gradual transition from the 'Bottom Up' strategy (based on what is easily feasible) to the 'Top Down' approach is required (based on the desired level of performance) (The World Bank, 2009). Abadi et al (2020) have classified the main studies in O&M management and used surveys to describe their findings and to represent future research opportunities in this field. Their study revealed the most frequently used terms in articles on O&M management in the Engineering Village -Elsevier database.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A self-healing data center is a data center that is capable of autonomously detecting potential component/module/hardware/software failures before they occur and adjust its configuration in order to achieve optimal function at all times [6]. The concept of detecting malfunctions and data center failures before they happen is called condition-based maintenance (CBM) or predictive maintenance (PdM) [7]. The approach requires a combination of historical, simulation, real-time information, expert heuristics, Fig.…”
Section: Introductionmentioning
confidence: 99%